Clinical Comparison of Renogen, a Biosimilar Epoetin-a, with the Originator, Eprex, in Chronic Kidney Disease Anemia in Indonesia: A Preliminary Study - Ni Made Hustrini; Parlindungan Siregar; Arini Setiawati; Pringgodigdo Nugroho (Acta Medica Indonesiana)
Background: treatment of erythropoietin (EPO) is essential in chronic kidney disease (CKD) patients to maintain optimal hemoglobin (Hb) level. Renogen is a biosimilar epoetin-α, and Eprex is the originator epoetin-α. This study aimed to compare the efficacy and tolerance of Renogen with Eprex in CKD anemia. Methods: Renogen and Eprex were compared in a randomized (2:1), open-label study for 8 weeks, proceeded by 4 weeks adjustment (maintenance) phase, in anemic CKD patients undergoing HD in Cipto Mangunkusumo General Hospital, Jakarta, from June 2017 to October 2018. Results: a total of 45 patients (31 received biosimilar EPO and 14 received originator EPO) were included in the study.  At baseline, mean (SD) Hb levels were 10.9 (0.74) g/dL and 10.9 (0.61) g/dL in biosimilar and originator EPO groups, respectively. At end of study (8 weeks), mean (SD) Hb levels were 10.5 (1.28) g/dL and 11.0 (1.13) g/dL in biosimilar EPO and originator EPO groups, respectively.  The proportion of patients with Hb levels maintained within the target range (>10 g/dL) during 8 weeks randomization phase were 58.1% and 71.4% in biosimilar EPO and originator EPO, respectively (p=0.60; NS). There were no significant difference in epoetin dose between the 2 groups, and there was no drug-related adverse event in either group. Conclusion: Hb level at >10 g/dL could be maintained for 8 weeks of treatment with both originator and biosimilar EPO (more consistent with originator EPO and more fluctuations with biosimilar EPO), with similar epoetin dose and no drug-related adverse event.